POPULATION DENSITY AND LENGHT -WEIGHT RELATIONSHIP IN MANGROVE GASTROPOD Cerithidea cingulata AND Littoraria scabra OF PANGKALAN SESAI VILLAGE, DUMAI CITY - Bariddah, Sania; Nasution, Syafruddin; Nedi, Syahril (Asian Journal of Aquatic Sciences, 2020)
Cerithidea cingulata and Littoraria scabra are type of snail that use mangrove ecosystems as one of their habitat. Dumai is one of the industrial cities in the province of Riau, where various kinds of human activities can disrupt the ecosystem of mangroves and its associated biota. This research was conducted in October 2018 in the Mangrove Forest Area (PAB) of Pangkalan Sesai village of Dumai City, aiming to determine population densities and length-weight relationship of C. cingulata and L. scabra. The method used in this study is a survey method. Sampling was conducted by using the line transect method, where each station consists of 3 transects and each transect consists of 3 sampling points as replications. The results showed the population density of C. cingulata and L. scabra snails was higher than at stations near the Dumai river estuary compared with the population near by mangrove forest and length-weight relationship showed that the growth patterns of both C. cingulata and L. scabra were allometric negative and have strong correlation value.